ANALISIS STATISTICAL LITERACY MAHASISWA MENGGUNAKAN SOAL TES TERINTEGRASI ISU PENDIDIKAN INDONESIA SEBAGAI WUJUD PENDEKATAN KONTEKSTUAL - Zulqoidi R. Habibie; Sundahry Sundahry; Masnia Masnia; Tasa Amanda (Jurnal Muara Pendidikan, 2024)
In this study, 116 students enrolled in Universitas Muhammadiyah Muara Bungo of School Teacher Education Study Programme (PGSD) will have their Statistical Literacy (SL) proficiency assessed using the Statistical Literacy Ability Test Questions integrated with Indonesian Education Issues using a quantitative descriptive research approach. Researchers used the interview technique to delve deeper into the data they collected, while descriptive analysis was done on the data collected through the distribution of test questions. The findings demonstrated that the students' Statistical Literacy still needed to be improved. On the Statistical Literacy ability exam, 75% of students who scored below 60 and 25% of students who scored over 60 showed these findings. Secondly, the average student's proficiency in answering SL test questions can be observed based on Indicators, which are 71.33% in Indicator 1, 53.16% in Indicator 2, and 57.18% in Indicator 3. In contrast, the average student's proficiency in answering SL questions is 28.67% in indicator 1, 46.84% in indicator 2, and 42.82% in indicator 3. According to in-depth interviews, the primary cause of students' low proficiency in SL is their need to master descriptive statistics. Conversely, the Indonesian Education Issue approach is the primary element contributing to students' capacity to solve SL questions. According to the findings of this study, more research is required to determine whether using learning models, creating new learning models, or using learning strategies to tackle SL challenges can help students' SL skills.